Modeling Of Groundwater By Using Finite Difference Methods And Simulation. - Baharum, Adam; AlQahtani, Hessah Faihan; Ali, Zalila; Lateh, Habibah; Koay, Swee Peng (2009)
In active landslide, the prediction of acceleration of movement is crucial issue for the design and performance of warning systems. Landslide occurs when a sudden increase beyond the critical level of groundwater. This is especially true in tropical weather during the wet season.